THE ROLE OF TRADITIONAL MARKET IN SUPPORTING ECONOMIC DEVELOPMENT IN SURAKARTA: CASE STUDY ON KLEWER MARKET IN SURAKARTA - Yosephine Angelina Yulia; Andry Oktaviani (Universitas Muhammadiyah Semarang, 2018)
Market is one of the activities trade that can not be separated from the daily activities of human life. The rapid development of population,so the need of market both in quantity and quality. The existence of traditionalmarkets and modern markets is already a part in the life of society urban areas. Some opinions assume that with the growing modern market, traditional market become more marginalized towards its renewal. For the communities Javanese, traditional market is just not as the place to buy and sell, but more that traditional market is related to the conception of life and social culture. The problem of research is how traditional markets can support economic at Surakarta. One of purposes of thereseach is exploring traditional market to do threaths, challenges to use potency an opportunity for supporting economic development at Surakarta. Method of reseach is SWOT analysis. There are some strategies for developin traditional market to support economicdevelopment are as follows :1. Preservation of historical value as cultural attractions, 2. Easy export-import facilitie, 3. Empowering the market community, 4.Optimizing management as a shopping object. Keywords: Traditional market, SWOT Analysis, Economic development.